Transcriptional stress responses to environmental and husbandry stressors in aquaculture species - Nour Eissa; Han‐Ping Wang (Reviews in Aquaculture, 2016)
Stress of aquatic animals occurs due to physical and physiological disturbances in the aquatic environment or system when transportation, crowding, handling or changes of physical and chemical factors take place. There are three regulatory systems having a vital role in stress response: the neural, endocrine and immune systems. Fish exhibit multiple genomic and physiological responses to adjust the compensatory or adaptive mechanism that allows them to mitigate the stressors, maintain their haemostasis and survive. In this review, we describe multiple important genes that are associated with responses to environmental and husbandry stressors and that could be used as biomarkers of environmental and husbandry stressors in fish. The described environmental and husbandry stressors include salinity, temperature, hypoxia and hyperoxia, confinement, density and handling. The main role of stress response in aquatic animals is to compensate or adapt their biological systems and arrange the metabolism to afford the energy required by the stressor and a wide array of metabolic processes and pathways are involved. We summarized and discussed highly significant genes in several organs and tissues that are involved and active during this adaption process. The traditional stress biomarkers in some circumstances have some difficulties in interpretation of results and lead to tricky diagnosis and searching and understanding alternative tools is critical for aquaculture, fisheries and fish welfare. Using genomic tools to study the candidate genes associated with stress responses are often unique signatures or imprints of specific stressors and could determine early signs of stressors.